Anaplerotic Pathways in Halomonas elongata: The Role of the Sodium Gradient - Hobmeier, Karina; Goëss, Marie C.; Sehr, Christiana; Schwaminger, Sebastian; Berensmeier, Sonja; Kremling, Andreas; Kunte, Hans Jörg; Pflüger-Grau, Katharina; Marin-Sanguino, Alberto (Frontiers in Microbiology, 2020)
Salt tolerance in the γ-proteobacterium Halomonas elongata is linked to its ability to produce the compatible solute ectoine. The metabolism of ectoine production is of great interest since it can shed light on the biochemical basis of halotolerance as well as pave the way for the improvement of the biotechnological production of such compatible solute. The ectoine production pathway uses oxaloacetate as a precursor, thereby connecting ectoine production to the anaplerotic reactions that refill carbon into the TCA cycle. This places a high demand on these reactions and creates the need to regulate them not only in response to growth but also in response to extracellular salt concentration. In this work we combine modeling and experiments to analyze how these different needs shape the anaplerotic reactions in H. elongata. First, the stoichiometric and thermodynamic factors that condition the flux distributions are analyzed, then the optimal patterns of operation for oxaloacetate production are calculated. Finally, the phenotype of two deletion mutants lacking potentially relevant anaplerotic enzymes: Phosphoenolpyruvate carboxylase (Ppc) and Oxaloacetate decarboxylase (Oad) is experimentally characterized. The results show that the anaplerotic reactions in H. elongata are indeed subject to different evolutionary pressures than those of other gram-negative bacteria. Ectoine producing halophiles must meet a higher metabolic demand for oxaloacetate and the reliance of many marine bacteria on the Entner-Doudoroff pathway compromises the anaplerotic efficiency of Ppc, which is usually one of the main enzymes fulfilling this role. The anaplerotic flux in H. elongata is contributed not only by Ppc but also by Oad, an enzyme that has not yet been shown to play this role in vivo. Ppc is necessary for H. elongata to grow normally at low salt concentrations but it is not required to achieve near maximal growth rates as long as there is a steep sodium gradient. On the other hand, the lack of Oad presents serious difficulties to grow at high salt concentrations. This points to a shared role of these two enzymes in guaranteeing the supply of OAA for biosynthetic reactions.